2009
DOI: 10.4081/ijas.2009.s2.721
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics of Amiata donkey reared in Tuscany

Abstract: In this work were studied morphological characteristics and biometric parameters of the Amiata donkey. The Amiata donkey is a local endangered breed and derives from the homonym mountain in Tuscany. This donkey, which was used, over the past, like pack animal in farms and in mines, is now involved in milk production, onotherapy and trekking. The averages and the standard deviations of the biometric parameters and the frequency of the morphological characters of foals, adult females and stallions were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 1 publication
4
10
1
1
Order By: Relevance
“…We also found that the classification accuracy in the Stepwise Forward Discriminant Analysis obtained with the model that included all studied morphological traits may also be achieved by applying the model that includes only four traits: hip height, croup width, body length and chest depth. These results highlight the redundancy of the majority of morphological traits used in our study, which are, more or less, similar to those commonly used for morphological characterization of donkey breeds (e.g., Folch & Jordana, 1997;Sargentini et al, 2009;Sargentini et al, 2018;Kefena et al, 2011;Kosuková et al, 2015;Labbaci et al, 2018;Ayad et al, 2019). Nonetheless, an important finding is that hip height/chest depth, croup width and body length are weakly correlated because these parameters (or parameters with which they are highly correlated) belong to different PCA-groups (Table S1).…”
Section: Morphological Characterization Of the Banat Donkeysupporting
confidence: 77%
See 2 more Smart Citations
“…We also found that the classification accuracy in the Stepwise Forward Discriminant Analysis obtained with the model that included all studied morphological traits may also be achieved by applying the model that includes only four traits: hip height, croup width, body length and chest depth. These results highlight the redundancy of the majority of morphological traits used in our study, which are, more or less, similar to those commonly used for morphological characterization of donkey breeds (e.g., Folch & Jordana, 1997;Sargentini et al, 2009;Sargentini et al, 2018;Kefena et al, 2011;Kosuková et al, 2015;Labbaci et al, 2018;Ayad et al, 2019). Nonetheless, an important finding is that hip height/chest depth, croup width and body length are weakly correlated because these parameters (or parameters with which they are highly correlated) belong to different PCA-groups (Table S1).…”
Section: Morphological Characterization Of the Banat Donkeysupporting
confidence: 77%
“…Their chest circumference is >20 cm wider, and their hips and withers are 8-15 cm higher than those measured in other studied groups. Body measurements of a single studied 8-years old Banat donkey male (Table 1) generally correspond to those recorded for younger females (average age 5.25 years), with a somewhat larger difference observed in body length, carpal circumference, chest depth, hip height and tibia circumference, which are the most common morphological traits used for donkey breed characterization (e.g., Folch & Jordana, 1997;Sargentini et al, 2009;Sargentini et al, 2018;Kefena et al, 2011;Kosuková et al, 2015;Labbaci et al, 2018;Ayad et al, 2019). This would indicate a possible sexual dimorphism in the Banat donkey which is indeed present in certain donkey breeds (e.g., Catalonian donkey from Spain, Folch & Jordana, 1997).…”
Section: Morphological Characterization Of the Banat Donkeymentioning
confidence: 57%
See 1 more Smart Citation
“…La taglia e gli indici biometrici dell'asino Calabrese sono sovrapponibili a quanto osservato da Di Rosa et al (2007) nell'asino Pantesco, ma inferiori rispetto a quelli osservati nella razza Romagnola (Beretti et al, 2005). L'asino dell'Amiata (Sargentini et al, 2009) ed il Grigio Siciliano (Liotta et al, 2005) nonostante mostrino un'altezza al garrese sovrapponibile a quella dell'asino Calabrese evidenziano invece diametri longitudinali minori, diversificandosi quindi come tipo morfologico. Gli indici biometrici ricavati (tabella II) ci hanno permesso, in linea di massima, di inquadrare questa popolazione asinina nel tipo dolicomorfo, anche se è emersa una certa variabilità all'interno del campione osservato, come riportato da Padula (1998) più elevato quanto minore è la compattezza del corpo) e dall'indice di ossatura (che esprime il grado di sviluppo scheletrico dell'animale).…”
Section: Risultati E Discussioneunclassified
“…The Amiata donkey shows the features of the ancestrals Equus asinus africanus and Equus asinus somaliensis (Sargentini et al, 2009). The african origin of Amiata donkey can also favor studies and search on donkeys in undeveloped countries.…”
Section: Introductionmentioning
confidence: 99%